The requirement for higher education for the officer corps of the Malaysian army - Akhbar Khan, Bibi Zarjaan (1998)
The requirement for tertiary education for officers in the Malaysian Armed Forces (MAF) has long been recognised. In the 1960s there was some form of tertiary education programme for selected officer cadets as well as young officers in the Engineer Corps and Electrical and Mechanical Engineer Corps of the Malaysian Army and corresponding branches in the Royal Malaysian Navy (RMN) and the Royal Malaysian Air Force (RMAF). Howevever, due to the absence of clear policy guidance and directives from the Armed Forces Council (AFC), which i s the highest governing body of the MAF. the programme unfortunately was haphazardly administered and experienced many problems. This led to the introduction of the Armed Forces Tertiary Education Scheme (AFTES) in 1980 with the fol lowing objectives: first, to meet the MAF requirement for qualified officers in the professional. managerial and technical fields: and second. to raise the general level of academic education of military officers so that the quality of military professionalism can be improved.